Co-carbonization of red mud and waste sawdust for functional application as Fenton catalyst: Evaluation of catalytic activity and mechanism. Issue 4 (August 2021) - Sun, Ruirui; Zhang, Xue; Wang, Chongqing; Cao, Yijun
Abstract: Synthesis of red mud/biochar (RMBC) composite was conducted by facile co-carbonization of red mud and waste sawdust. Multiple characterizations verify the reduction of ferric oxide and the formation of graphitic biochar with defects. Hydrogen peroxide activation by RMBC was investigated for Rhodamine B (RhB) oxidation. RMBC displays both adsorption and catalytic effects for RhB removal. Catalytic oxidation of RhB is effectively obtained at pH below 2.2. RhB oxidation is slightly improved with growing temperature. RhB oxidation in RMBC/H2 O2 system obeys the pseudo first-order kinetic, and the low activation energy of 56 kJ/mol implies the effective hydrogen peroxide activation by RMBC. Associated with the determinations of radical and iron leaching, the dominant role of hydroxyl radical in solution is verified for RhB oxidation. The limitation of RMBC for heterogenous catalysis may be solved by the regulation of alkaline feature. RMBC processes special properties of red mud and biochar, and its application to wastewater treatment provides a green and sustainable approach obeying the "waste treating waste" concept. Graphical Abstract: Co-carbonization of red mud and waste sawdust as Fenton catalyst for Rhodamine B oxidation in aqueous solution ga1 Highlights: Red mud-biochar composite was synthesized by facile co-carbonization. Multiple characterizations indicate Fe3 O4 and graphitic biochar with defects. Fenton oxidation of Rhodamine B was effectively obtained at low pH. The dominant role of ·OH in solution is verified in RhB oxidation. This work offers a sustainable strategy of "waste treating waste".